Surface integrity study of WEDM with various wire electrodes: experiments and analysis. Issue 4 (3rd July 2020) - Sen, Ruma; Choudhuri, Bikash; Barma, John Deb; Chakraborti, Prasun
Abstract: Wire electrical discharge machining (WEDM) is always significant for its high-precision machining. However, due to the generation of high discharge energy during machining, machined surfaces are often got distorted. These might be upgraded by choosing the correct tool with proper machining condition. The effects of the electrode materials and process parameters on different responses of WEDM like average surface roughness, recast layer thickness, and surface morphology are systematically examined here to enhance the knowledge of WEDM and its correlation with electrode property. The experiments have been carried out on one of the expensive steel namely Maraging steel 300 due to its applicability in tooling and aerospace industries. Plain brass wire, zinc-coated brass wire (ZCB), and silver-coated brass (SCB) wires are used as a tool electrode for analysis. Comparative experimental studies prove that among BW, ZCB, and SCB, the overall performance of SCB is commendable owing to the high-quality surface considering control parameters in low discharge energy level. However, the second-best performance is shown by ZCB.